Two-year comparative study on immediate versus delayed induction in term premature rupture of membranes - Betty Agnes, John Mary; Lavanya, Sowmyanarayanan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Premature rupture of membranes (PROM) has an incidence of about 10% of all pregnancies and is a significant event as it can cause maternal complications, neonatal morbidity and mortality. Some believe that the expectant management of PROM at term does not increase the perinatal and maternal morbidity, and immediate induction of labour leads to an increased caesarean section rate. There are some authors who report a significant increase in the rates of neonatal, maternal infection and foetal distress if delivery occurs over 24 hours after PROM. Thus, a data is required to manage the cases of PROM to effect safe delivery for both mother and baby. The objective of the study was to compare the neonatal and maternal outcomes between immediate and delayed induction with PG E2 gel in term PROM. Methods: A hospital based study in women admitted to Obstetrics and Gynaecology Department at R.S.R.M Hospital with a sample of 400 patients in age group between 19- 35 years with gestational age between 37 and 41 weeks were selected for the study. All the 400 cases who presented with term PROM were admitted in labour room and history was elicited regarding age, menstrual and obstetric history with enquiry regarding the time of rupture of membranes, duration and amount of leaking with general, systemic and detailed obstetric examination. Results: The number of PG E2 gel needed for induction varied between the two groups. Around 45 patients in group 2 needed second dose of gel whereas only 32 patients required the second dose in the late induction group and 72 cases got into active labour. There was no difference in maternal and neonatal infectious morbidity between the two groups. This may be due to the use of prophylactic antibiotics. Neonatal outcome was equally good in both the groups. Conclusions: Delayed induction of labour in PROM after a waiting period of 12 hours stands as a reasonable option as it reduces the number of operative deliveries without compromising the maternal and neonatal outcome.